EFEKTIVITAS PENGGUNAAN KORTIKOSTEROID TERHADAPPASIEN COVID-19 DERAJAT BERAT DENGAN ARDS: Tinjauan Sistematik - Soraya Maulidina (2022)
Introduction: ARDS is a major complication of COVID-19 infection and is associated with a high mortality rate. Currently, no definitive therapy has been shown to reduce ARDS-related mortality with either COVID-19 or non-COVID-19 etiology. The mechanism COVID-19 progresses to ARDS is thought to be due to a cytokine storm. The anti-inflammatory effect of corticosteroids may reduce pulmonary and systemic hyperinflammation due to increased secretion of proinflammatory cytokines. This systematic review will review the effectiveness of using corticosteroids in severe COVID-19 patients with ARDS. Method: A systematic review was conducted by searching the literature on Pubmed and Google Scholar databases with reference to the PRISMA-P method. The literature obtained was then selected through the JBI Critical Appraisal Checklist. Results: administration of corticosteroids with low-high doses of IV methylprednisolone 0.6 - 8 mg/kg/day or high doses of IV dexamethasone 10 - 20 mg/day for 10 days during the early phase of ARDS or risk of developing ARDS (clinical worsening >7 days of onset symptoms) or >72 hours of hospitalization yielded beneficial outcomes in severe COVID-19 patients with ARDS. Corticosteroids were associated with a decreased blood CRP levels, improved ventilation and oxygenation, but did not reduced the risk of mortality and decrease the duration of hospitalization. Conclusion: the use of corticosteroids helps to provide beneficial outcomes in severe COVID-19 patients with ARDS